Problems and responses of schools in the COVID -19 pandemic: The case of Mountain Province - Pangket, Willow F (International Journal of Innovative Research and Scientific Studies, 2023)
This study explored the problems faced by the schools in Mountain Province, Philippines with the implementation of distance education during the pandemic and looked into the schools' good practices to mitigate the problems. 26 schools participated in this study. Analysis of the data gathered highlighted the serious problems in Philippine education. The problems faced by the schools during the pandemic are similar to those faced by developing countries, however, the problems and responses faced by the schools in Mountain Province are specific to their context. The common problems identified during this pandemic are: difficulty in distributing and retrieving modules, unavailability of equipment and gadgets, poor internet access, poor quality of learning materials, the unpreparedness of parents taking on the role of teachers, teachers' lack of training on the modality of learning, lack of technological knowledge, a one-size-fits-all approach to instruction, an inadequate learning management plan for blended learning and the decreased income of private schools. The good practices implemented by the schools to address some of their problems are: home visits, tutorials, Parent-Teacher Association (PTA) involvement, remediation classes, a seminar on stress management and mechanisms for blended learning. There is a need for the school administration to provide learning management plans which should include short and long-term goals and professional learning initiatives like training to improve teachers' technological pedagogical knowledge.